2017
DOI: 10.1159/000480212
|View full text |Cite
|
Sign up to set email alerts
|

Mir-22-3p Inhibits Arterial Smooth Muscle Cell Proliferation and Migration and Neointimal Hyperplasia by Targeting HMGB1 in Arteriosclerosis Obliterans

Abstract: Background: Aberrant vascular smooth muscle cell (VSMC) proliferation and migration contribute to the development of vascular pathologies, such as atherosclerosis and postangioplasty restenosis. The aim of this study was to determine whether miR-22-3p plays a role in regulating human artery vascular smooth muscle cell (HASMC) function and neointima formation. Methods: Quantitative real-time PCR (qRT-PCR) and fluorescence in situ hybridization (FISH) were used to detect miR-22-3p expression in human arteries. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 46 publications
2
52
0
Order By: Relevance
“…This notion was strongly supported by a recent study showing higher serum HMGB-1 levels in patients with type 2 diabetes affected by PAD [93]. Furthermore, the expression of HMGB-1 increased in diabetic foot atherogenesis and arteriosclerosis obliterans [94,95].…”
Section: Figmentioning
confidence: 58%
“…This notion was strongly supported by a recent study showing higher serum HMGB-1 levels in patients with type 2 diabetes affected by PAD [93]. Furthermore, the expression of HMGB-1 increased in diabetic foot atherogenesis and arteriosclerosis obliterans [94,95].…”
Section: Figmentioning
confidence: 58%
“…HMGB1 is highly expressed in human atherosclerotic lesions and it has been involved in arteriosclerosis . For instance, miR‐22‐3p can repress arterial smooth muscle cell proliferation and migration by targeting HMGB1 in arteriosclerosis . MiR‐126 inhibits inflammation in endothelial cells through targeting HMGB1 .…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] For instance, miR-22-3p can repress arterial smooth muscle cell proliferation and migration by targeting HMGB1 in arteriosclerosis. 30 MiR-126 inhibits inflammation in endothelial cells through targeting HMGB1. 31 MiR-24 depresses vascular smooth muscle cell proliferation and migration by reducing HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a growing body of recent data has shown that circulating miRs could influence the development and progression of vascular diseases, including atherosclerosis [24,25]. Although atherosclerosis is common in clinical practice, the mechanisms of its genesis have …”
Section: Discussionmentioning
confidence: 99%